Positive classroom climate buffers against increases in loneliness arising from shyness, rejection sensitivity and emotional reactivity - Katulis, Gintautas; Kaniušonytė, Goda; Laursen, Brett (Frontiers in Psychiatry, 2023)
Loneliness is detrimental to well-being, particularly during the transition into and early years of adolescence when peer relations are ascendant. Shy and emotionally sensitive youth, who often spend considerable time alone, have known vulnerabilities to loneliness. Studies of young children suggest that a supportive classroom context may mitigate adjustment risks, reducing victimization and improving a sense of belonging. Herein we extend this work to older students, testing the hypothesis that a positive classroom climate protects temperamentally vulnerable children (i.e., those who are shy, emotionally reactive, or sensitive to rejection) from escalating levels of loneliness across the course of a school year. A community sample of 540 (277 boys, 263 girls) Lithuanian students in grades 5–7 (10–14 years old) completed identical surveys twice, 4–5 months apart. Self-reports assessed shyness, emotional reactivity, and rejection sensitivity, as well as perceived positive classroom climate and loneliness. Path analyses indicated that longitudinal associations from shyness, emotional reactivity, and rejection sensitivity to increased loneliness were mitigated by positive classroom climate. In each case, temperamental vulnerability anticipated greater loneliness for youth reporting low but not high positive classroom climate. The results held after accounting for several potential confounding variables. The findings have practical implications, suggesting that scholars and practitioners redouble efforts to improve classroom support, particularly for temperamentally vulnerable children who are at elevated risk for solitude, loneliness, and attendant mental health challenges.